REINTERPRETASI IMAJINASI MASKULINITAS DARI PERSPEKTIF TEOLOGI KERAPUHAN - Kaseh, Novalin (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
This article aims to reinterpret the imagination of masculinity (Toxic Masculinity) with Theology of Vulnerability as the analytical tool. Focusing on the problem of suicide cases in the world which is still very worrying, including in Indonesia itself, this article argues that one of the reasons is because of this Masculinity Imagination. Quoting data from the World Health Organization (WHO) 2021 Global Health Estimates, of the 6,544 suicides across all ages in Indonesia, 5,095 cases occurred in men. The construction of men must not cry, must be strong, not weak, places them in an excessive imagination of